The Christmas Story - Yenne, Bill; Nang ChanYeema (Nashville, Tennessee, United States Thomas Nelson, 1993)
Simple text describes the birth of Jesus on the first Christmas an recounts who came to see him.
Keywords: Juvenile Nonfiction